Implementation of Islamic Education-Based Counseling to Overcome Social Problems in Children at Panti Asuhan Putera Bonang - Khairullah Khairullah (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to explore the implementation of guidance and counseling services in addressing social problems experienced by children at the Panti Asuhan Putera Bonang Banjarmasin (Putera Bonang Orphanage in Banjarmasin City) through the approach of Islamic religious education. The research uses a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings show that guidance and counseling services play a significant role in helping children overcome issues such as lack of discipline, low self-confidence, and difficulties in social interaction. By integrating Islamic values into the counseling process, children develop better behavior, emotional control, and social awareness. The approach also strengthens their spiritual foundation, which contributes positively to their overall character development. The study concludes that an Islamic education-based counseling approach is effective in shaping the moral and social behavior of children in orphanage environments.